(m-3)/(5+2)=m/6

Simple and best practice solution for (m-3)/(5+2)=m/6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (m-3)/(5+2)=m/6 equation:



(m-3)/(5+2)=m/6
We move all terms to the left:
(m-3)/(5+2)-(m/6)=0
We add all the numbers together, and all the variables
(m-3)/7-(+m/6)=0
We get rid of parentheses
(m-3)/7-m/6=0
We calculate fractions
There is no solution for this equation

See similar equations:

| F(t)=100-4.9^2 | | 9(x–4)–3x=18x= | | 9a+4=5a+48 | | |2x-10|=20 | | 2c-25+c-36+c-23=180 | | 5x+3x=230-2x | | 18x+51=70 | | 10+1.5r=25 | | 135=4x-1+86 | | (9x-x)4=(22+10) | | -10x+14=84 | | (x)+(x-7)+(2x-21)=180 | | 15=27=7d-3d | | 24=-8t-8 | | 4x-1=221 | | 3u+2u+u+18=180 | | 7x-6=63 | | (3x-7)/(x+4)=2 | | (10+x)(14+x)=221 | | 3(4x+7)=5x+13 | | 12h-14h=-14 | | 0.5(x−6)=0.1(5x−6) | | w+3-5=10 | | (4x-20)=(3x-6) | | 0.5(x−6)=0.25(2x−12) | | )3x-4)+(5x+1)+(7x-27)=180 | | 3x0.028=0.034 | | 4j-4j+3j=18 | | 86+n/6=74 | | 4x-1+86=135 | | 66+x=30° | | 38=2x+5 |

Equations solver categories